2019
DOI: 10.3171/2019.2.focus18724
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and monosegmental fusion for lumbar spondylolisthesis with a long tab percutaneous pedicle screw system: “swing” technique

Abstract: OBJECTIVEWith the development of minimally invasive procedures, percutaneous pedicle screw systems have been used to attempt to correct spondylolisthesis. No previous studies have reported on reduction measures using long tab percutaneous pedicle screws for spondylolisthesis. Additional intraoperative correction has been proposed with the “swing” technique. This study was conducted to compare the efficacy of standard minimally invasive transforaminal interbody fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Reduction screws are used in the thoracolumbar spine in instances of trauma and spondylolisthesis for both open and minimally invasive surgical applications. 24 , 25 Until recently, reduction screws have not been available for the cervical spine, which changed in 2019 with the approval of the Symphony OCT system (DePuy Synthes) by the Food and Drug Administration. These are polyaxial screws that allow 10 mm of threaded reduction over the length of the tulip head.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction screws are used in the thoracolumbar spine in instances of trauma and spondylolisthesis for both open and minimally invasive surgical applications. 24 , 25 Until recently, reduction screws have not been available for the cervical spine, which changed in 2019 with the approval of the Symphony OCT system (DePuy Synthes) by the Food and Drug Administration. These are polyaxial screws that allow 10 mm of threaded reduction over the length of the tulip head.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was performed by a single surgeon at a single institute who has written numerous articles about MIS-TLIF and has obtained more than 15 years of experience with performing MIS-TLIF operations. 5 6 24 25 26 27 28 The surgical techniques for MIS-TLIF were the same as those described in our previous study. 5 6 25 We also performed contralateral decompression, although contralateral facets were not removed.…”
Section: Methodsmentioning
confidence: 99%
“… 5 6 24 25 26 27 28 The surgical techniques for MIS-TLIF were the same as those described in our previous study. 5 6 25 We also performed contralateral decompression, although contralateral facets were not removed. We used a specific process to place cages more anterior for more effective creation of lordosis.…”
Section: Methodsmentioning
confidence: 99%
“…Study conducted by Park et al [ 17 ] used minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) mono-segmental reduction in lumbar spondylolisthesis. This study used long tab type percutaneous screw system regarding its simplicity and similarity to conventional pedicle screw system, but easier for manipulation in the last step of surgery.…”
Section: Management Of Spondylolisthesismentioning
confidence: 99%
“…This study includes only patients with Meyerding grade I or II. Swing technique resulted in better improvement of degree of spondylolisthesis and reduction rate compared to conventional screw systems [ 17 ]. Other studies also showed successful procedure in high-grade spondylolisthesis [ 18 ].…”
Section: Management Of Spondylolisthesismentioning
confidence: 99%